Penelitian Multidimensi: Analisis Beragam Jenis dan Teknik - Ramli, Ramli; Wahyuni, Andi Eki Dwi; Sulaiman, Umar; Rahman, Ulfiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to explore various types of research that can be used in the research process. This research was conducted through a qualitative approach with the literature stud method. The main sources of data for this research are various scientific articles, research results, and reference books that are relevant to the focus of this research. Scientific articles come from various credible and valid journal sources. Data analysis was carried out qualitatively consisting of data reduction, data presentation and conclusion drawing. . Based on the results of the analysis, it can be concluded that research can be classified based on approaches, namely qualitative and quantitative, based on place, namely literature research and field research, based on function, namely pure science research and applied research, based on objectives, namely descriptive research, correlative research, and comparative research. Based on methods, namely case research and survey research, historical research, sociological research, and explanatory research. In addition, there is also extraterrestrial research that can be used for proof, as well as R&D research and classroom action research applied in educational research